Project Management Methodologies for Engineering KMS based on PMBOK Approach: A Systematic Literature Review - Oki Priyadi; Dana Indra Sensuse (Proceeding of International Conference on Information Science and Technology Innovation (ICoSTEC), 2022)
The process of creating, sharing, discovering, and capturing knowledge becomes an intangible asset for an organization. As a valuable asset, Knowledge needs to be managed. There is a tool called Knowledge Management System (KMS). The latest technology and social or structural mechanisms are components to develop KMS. But developing an IT project has a high risk of failure, so it should be managed using a project management approach. A project is a temporary endeavor to make a product or service. It means that a project has a start and an end project phase. Some methodologies which exist do not offer complete stages of development KMS. They do not cover feasibility study activities, lack of clear specification, and lack of closing project phase. The study gap is expected to be loaded up and well explained in this paper through a systematic review of the published literature over the last six years using the Kitchenham method. The results show that most researchers used a predictive approach compared to an iterative, incremental, or adaptive development approach to build KMS. The main result of this study we found 36 processes in the developing KMS. The novelty of this research, we generated a table to map the processes into the model, method, artifact and presented it by group process based on the Project Management Body of Knowledge (PMBOK). The table can help the organization develop the KMS project to improve its effectiveness and competitiveness.